A Novel Approach for Color Image Edge Detection Using Multidirectional Sobel Filter on HSV Color Space - Bora, Dibya Jyoti (International Journal of Computer Sciences and Engineering, 2025)
Edge detection is a very commonly adopted operation in any pattern recognition task like image segmentation as edges are the prominent features which form the outlines in an image. Detecting edges for a color image is a bit difficult than the same in a gray image. In this paper, a novel approach for edge detection in color images is proposed. This approach is based on Multi-directional Sobel filter. For the color arrangement, HSV color space is used. The experimental results demonstrate the efficiency of the proposed approach.